SOCIALIZATION OF CLEAN AND HEALTHY LIFESTYLE BEHAVIOR IN SDN 8 SIANTING-ANTING SAMOSIR REGENCY: SOCIALIZATION OF CLEAN AND HEALTHY LIFESTYLE BEHAVIOR IN SDN 8 SIANTING-ANTING SAMOSIR REGENCY - Siallagan, Ance M; Sijabat, Anita; Simbolon, Frans Santo; Napitupulu, Devita Winda; Simarmata, Ruth Elovani; Sagala, Erosima; Nadeak, Verawati (JURNAL PENGMAS KESTRA (JPK), 2022)
Improving health status is one of the national development efforts to create a healthy, prosperous Indonesian society. Clean and healthy living behavior (PHBS) is an action to empower elementary school students to be able and willing to carry out clean and healthy living behaviors so as to create a healthy school environment. This community service activity aims to provide socialization and education for students at SD Negeri number 8 Sianting-anting, Samosir Regency. Activities consist of socialization in the form of counseling, discussion and question and answer. The activity participants consisted of 71 students from grades 1 to 6. The material presented was how to wash hands with soap and running water, consume healthy snacks, use clean and healthy latrines, exercise regularly, eradicate mosquito larvae, smoke free at school, dispose of trash in its place and work together to keep the school environment clean. Participants were very enthusiastic and gave positive responses and actively participated in socialization activities. The results of the activity evaluation showed that the participants were able to wash their hands properly, mentioned the PHBS components at school, and after the socialization activities, students also implemented PHBS at SDN 8 Sianting-anting, Samosir Regency. The statistical test using the t-paired test showed that the value of p = 0.001 (p <0.05) which means that there is a difference before and after being given PHBS education on the level of knowledge of students at SDN 8 Sianting-anting, Samosir Regency.